Recognition and localization method of maize weeding robot based on improved YOLOv5 - Zhao, Lijun; Jia, Yunfan; Yin, Wenke; Li, Zihuan; Liu, Chuandong; Luo, Hang; Hu, Xin; Huang, Hua; Li, Qiang; Lyu, Cheng; Li, Bin (International Journal of Agricultural and Biological Engineering, 2025)
In response to the challenge posed by low recognition accuracy in rugged terrains with diverse topography as well as feature recognition agricultural settings, this paper presents an optimized version of the YOLOv5 algorithm alongside the development of a specialized laser weeding experimental platform designed for precise identification of corn seedlings and weeds. The enhanced YOLOv5 algorithm integrates the effective channel attention (CBAM) mechanism while incorporating the DeepSort tracking algorithm to reduce parameter count for seamless mobile deployment. Ablation tests validated this model’s achievement of 96.2% accuracy along with superior mAP values compared to standard YOLOv5 by margins of 3.1% and 0.7%, respectively. Additionally, three distinct datasets captured different scenarios, and their amalgamation resulted in an impressive recognition rate reaching up to 96.13%. Through comparative assessments against YOLOv8, the model demonstrated lightweight performance improvements, including a notable enhancement of 2.1% in recognition rate coupled with a marginal increase of 0.2% in mAP value, thus ensuring heightened precision and robustness during dynamic object detection within intricate backgrounds. Key words: precision agriculture; YOLOv5; weeding robot; maize; laser weedingDOI: 10.25165/j.ijabe.20251802.9463Citation: Zhao L J, Jia Y F, Yin W K, Li Z H, Liu C D, Luo H, et al. Recognition and localization method of maize weeding robot based on improved YOLOv5. Int J Agric & Biol Eng, 2025; 18(2): 248–258.